2014
DOI: 10.1186/1477-7819-12-306
|View full text |Cite
|
Sign up to set email alerts
|

Ileocolonic anastomosis after right hemicolectomy for colon cancer: functional end-to-end or end-to-side?

Abstract: BackgroundThe purpose of this study was to compare short-term clinical outcomes of ileocolonic functional end-to-end anastomosis (FEEA) and end-to-side anastomosis (ESA) following resection of the right colon for cancer.MethodsWe enrolled 379 patients who underwent ileocolonic anastomosis following resection of the right colon for cancer by a single surgeon, from January 2009 through June 2012. Patient characteristics, operative results, and postoperative complications were analyzed.ResultsA total of 164 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
11
2
Order By: Relevance
“…The effectiveness of this technique was reported also by Liu et al . 20 Our results do not confirm the association between the postoperative results and blood transfusion suggested by Marinello et al . 14 Despite being a significant predictor in the univariable analysis, blood transfusion was not an independent predictor of complications in the multivariable model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of this technique was reported also by Liu et al . 20 Our results do not confirm the association between the postoperative results and blood transfusion suggested by Marinello et al . 14 Despite being a significant predictor in the univariable analysis, blood transfusion was not an independent predictor of complications in the multivariable model.…”
Section: Discussioncontrasting
confidence: 99%
“…We believe that single-layer suture is a simple technique that significantly expedites the procedure, while the endto-end anastomosis avoids the need for additional closure of the intestinal stumps on the proximal and/or distal loops. The effectiveness of this technique was reported also by Liu et al 20 Our results do not confirm the association between the postoperative results and blood transfusion suggested by Marinello et al 14 Despite being a significant predictor in the univariable analysis, blood transfusion was not an independent predictor of complications in the multivariable model.…”
Section: Discussioncontrasting
confidence: 83%
“…Surgical assessment was also performed for the studied patients, focusing on the circumstances and technical aspects of the anastomoses. At the beginning, we analyzed the execution modality, observing that S-E technique is associated with the highest risk of developing anastomotic fistula, being calculated statistically significant odds, while other authors described that E-S variety has the highest risk of association with an anastomotic leakage (13); also, we observed that S-S technique presents the lowest chances of anastomotic leakage and could be considered a protective factor in the development of the fistula (14). Regarding the anastomotic suture layers, we observed similar results concerning single layer and double layer anastomoses, the number of layers showing no influence in the progression through leakage, our results being in accordance to other field researches, which also affirmed no significant differences between suturing in single or double layer (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still controversies regarding ileo-colonic anastomosis after right hemicolectomy. According to Liu et al [ 8 ], side to side mechanic anastomotic technique is preferred, while Nordholm-Carstensen et al [ 9 ] sustained that stapled anastomosis had higher rates of AL after right colectomy. Meantime, others stated that handsewn and stapled techniques can be performed with a very low risk of anastomotic leak [ 10 ].…”
Section: Discussionmentioning
confidence: 99%